THE RAPID CHANGES OF THE U.S. FOREIGN MILITARY ASSISTANCE TO UKRAINE IN 2019: A NEOCLASSICAL REALISM PERSPECTIVE - Rangga Amalul Akhli (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
In the US fiscal year 2019, Trump and the US Congress agreed to provide foreign military assistance funds approximately $400 million to Ukraine. In its distribution process, Trump procrastinated the release as he decided to halt that in July. Two months later, he changed it and released the assistance. This study seeks to analyze the dynamics of that rapid change policy. In doing so, it employs qualitative research, particularly the process-tracing method as its function to trace the causal mechanism of the research puzzle. By applying Neoclassical Realism provided by Ripsman, Taliaferro, and Lobell, this paper demonstrates some findings:  The halt policy is regarding Trump's political endeavor to weaken and outperform his domestic political rival, the Democratic Party. Trump asked the Ukrainian counterpart to investigate Joe Biden's corruption and reverted Russia hack scandal in the last US presidential election in exchange for the release of military assistance. However, the policy was hampered by some domestic elements, (1) some of the Foreign Policy Executive thought the halt policy was not following the US national security, hence they acted as whistleblowers issuing Trump personal interest in the issue to gain wider public awareness; (2) US Strategic Culture, a perception that shapes Russia as among US enemy. Thus, that halt policy is perceived against US collective value; (3) US check and balance system; (4) Trump consideration that the halt policy can jeopardize his position as president in the next election. These factors contribute to the release of assistance.